Um modelo de controle integrado (químico e biológico) via Programação Linear Fuzzy para a lagarta-do-cartucho Spodoptera frugiperda (Lepidoptera: Noctuidae) na cultura do milho - Santos, Patrícia do Nascimento dos (Universidade Federal de São Carlos, 2022)
This work aims to propose a mathematical model for optimal pest control in agriculture via integration of chemical (application of insecticides) and biological (predation and/or parasitism) control strategies with optimization techniques via Linear Programming Fuzzy . Its main objective is apply this model to the control of the fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae), a consolidated pest in Brazilian territory. Agribusiness plays an important role in the Brazilian economy, exerting a relevant influence on the Gross Domestic Product. Currently, the country is one of the great exporters of agricultural products, focusing on corn, one of its main crops, leading the world export in 2019, surpassing previously exported quantities. According to projections for the next decade, the expectation is that the demand for agricultural production will grow driven by population and income growth, consequently increasing the need for risk management that minimizes costs and maximizes productivity. One of the major problems is associa- ted with the incidence of pests in the plantations, considering that the costs related to control are high, especially the chemical one. Therefore, the adhesion of new techniques is indispensable and the Integrated Pest Management proves to be efficient, as in addition to generating less environmental impact, it combines different strategies, such as biological control.
An integrated control model (chemical and biological) via fuzzy linear programming for \textit{Spodoptera frugiperda} (Lepidoptera: Noctuidae)
Keywords: Controle; Predação; Parasitismo; Conjuntos Fuzzy; Programação Linear Fuzzy; Control; Predation; Parasitism; Fuzzy Sets; Linear Programming Fuzzy; CIENCIAS EXATAS E DA TERRA::MATEMATICA